Retaining Talent: The Impact of Entrepreneurial Leadership in Indonesian Startup Companies - Qibtiyah*, Mariah Rabiatul; Salsabil, Imanirrahma (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2023)
This study aims to explore the indirect influence of entrepreneurial leadership on employee turnover intention through affective commitment while examining the moderating effect of perceived organizational support. The Structural Equation Modeling (SEM) approach was employed with 120 respondents in startup companies. The results indicate that entrepreneurial leadership has a negative and significant influence on employee turnover intention, with affective commitment mediating this relationship. Furthermore, perceived organizational support significantly moderates the negative correlation between affective commitment and turnover intention. The implication is that startup companies can reduce employee turnover intention to operate more effectively. Keywords: Affective Commitment; Entrepreneurial Leadership; Perceived Organizational Support; Startup; Turnover Intention